An analysis on the lift generation for Coandă micro air vehicles - Djojodihardjo, Harijono; Ahmed, Riyadh Ibraheem; Yousefian, Ali (IEEE, 2014)
A mathematical model for lift generation on a doughnut-shaped Coandă micro air vehicle is developed and an analysis on the lift generation due to Coandă effect is carried out utilizing basic principles. A degenerate two-dimensional case is also developed. The results are discussed in view of related analytical and experimental work in the literature.